A simple synthesis of urchin-like Pt–Ni bimetallic nanostructures as enhanced electrocatalysts for the oxygen reduction reaction. Issue 3 (10th November 2015) - Choi, Kwang-Hyun; Jang, Youngjin; Chung, Dong Young; Seo, Pilseon; Jun, Samuel Woojoo; Lee, Ji Eun; Oh, Myoung Hwan; Shokouhimehr, Mohammadreza; Jung, Namgee; Yoo, Sung Jong; Sung, Yung-Eun; Hyeon, Taeghwan
Abstract : Pt–Ni nanostructures have superior oxygen reduction reaction activities. Abstract : The synthesis of urchin-like Pt–Ni bimetallic nanostructures is achieved by a controlled one-pot synthesis. Pt–Ni nanostructures have superior oxygen reduction reaction activities in both with and without specific anion adsorption electrolytes due to the geometric and alloying effects.